An Analysis of the Picture and Picture Model as a Remedial Approach for Enhancing Comprehension of Scientific Concepts - Rini Endah Sugiharti; Deden Dicky Dermawan; Annis Kandriasari (Indonesian Journal of Primary Education, 2023)
This study aims to ascertain and scrutinize the augmentation of students' conceptual understanding within the domain of science education through the implementation of the picture and picture learning model. Science learning, a pivotal subject in elementary education, imparts knowledge about various natural phenomena by leveraging the outcomes of empirical discoveries, experiments, and direct observations conducted by students. Employing a data analysis process, this research places significant emphasis on extracting comparative insights gleaned from an extensive review of scientific journals. Data for this study were sourced from reference journals, online databases, and national and international journal collections. The findings reveal that the integration of the picture and picture learning model is associated with an elevated level of student comprehension in science concepts. Moreover, this pedagogical approach fosters active student engagement, rendering the classroom environment more dynamic and enjoyable. Consequently, the study concludes that the picture and picture learning model serves as a viable solution for enhancing science conceptual understanding in elementary education